Journey to Solla Sollew: Teacher Candidates, Resiliency, and Children's Literature - Gayla Lohfink; Susan Unruh (The Advocate, 2013)
Today’s elementary student must learn coping strategies in order to deal with life’s challenges—social, emotional, and academic—in his or her changing world. To foster the development of such learning, teacher preparation programs must include instruction in which teacher candidates study how to facilitate their students’ awareness of mechanisms for recovering from life’s setbacks and show resiliency. This article presents a training module for enhancing pre-service teachers’ pedagogical knowledge of resiliency. Examples of recent publications of children’s literature are shared and modeled as lessons to exemplify how this particular resource can be used to encourage resiliency in children.